Ayurvedic Management of Aamvata (Rheumatoid Arthritis) (AYUSHDHARA, 2025)
Aamvata, a condition described in Ayurveda, closely resembles Rheumatoid Arthritis (RA) in modern medicine. It is characterized by the accumulation of Ama (undigested metabolic waste) and Vata (bio-energy responsible for movement), leading to joint inflammation (Sandhishoth), pain (Shoola), stiffness (Stabdhata) and systemic symptoms like fever and digestive disturbance. Conventional treatment of RA primarily involves Disease-Modifying Anti-Rheumatic Drugs (DMARDs) and NSAIDs, which may have long-term side effects. Ayurveda offers a holistic approach through Shodhana (purification), Shamana (palliative care), diet, and lifestyle modifications. This case report highlights the successful Ayurvedic management of Aamvata in a 53-year-old male patient seen in the 18th number OPD of Kayachikitsa Department at Govt. Auto. Dhanwantari Ayurveda Medical Hospital, Ujjain (M.P.) His chief complaints Agonising joint pain or fleeting pain (Vrushchikdanshvat Vedana), pain in both legs, pain referred to the knee joint and ankle joint, indigestion, anorexia, constipation, low grade fever, morning stiffness more than 30 minutes.